Noninvasive predictors of large esophageal varices: is there an emerging role of aspartate aminotransferase-to-platelet ratio index in hepatocellular carcinoma? - Heba Sedrak; Rania Khalifa; Ahmed Elkafrawy; Hany Elewa (SpringerOpen, 2015)
Background and aim Variceal size has been identified to be closely related to variceal bleeding. Repeated endoscopic examinations have a great burden on endoscopic units and cost-implication issues. Our aim was to evaluate the role of AST to platelet ratio index (APRI) in predicting the existence of large esophageal varices (EV) in hepatitis C virus-related liver cirrhotic patients. Patients and methods Seventy four patients with liver cirrhosis were prospectively recruited. Laboratory data, CTP, MELD and APRI, also ultrasonographic and endoscopic findings are performed and investigated whether associated with the size and bleeding of EV. Results Patients were divided into two groups; group 1 with small varices and group 2 with large varices. Group 2 had significantly prolonged prothrombin time, splenomegaly, ascites, higher Child score compared to group 1. CTP was associated with variceal bleeding (P = 0.028). While APRI was a poor predictor both for the presence of LVs and bleeding yet it revealed favorable Results with bleeding EVs in patients with HCC with AUC (0.61). APRI was a good predictor for the presence of HCC and number of focal lesions with AURC (0.651, 0.61 respectively). Conclusion Splenomegaly, CTP, ascites could be used as noninvasive predictors for large EVs. However, at the moment, these tests could not substitute for endoscopy. Although APRI is a poor predictor for the size and bleeding of EV, yet it might have a role in prediction of HCC and number of focal lesions.